Strategic integration of data envelopment analysis and backcasting theories for zero-emission transition in global container shipping companies: pathways and frameworks - Sim, Min-seop; Lee, Jeong-min; Kim, Yul-seong; Jung, Dong-ho; Lee, Chang-hee (Frontiers in Marine Science, 2025)
While previous research on environmental efficiency examines data from the annual reports of shipping companies, this study takes a novel approach. It applies data envelopment analysis (DEA) and backcasting theory to assess environmental efficiency and plan the transition to cleaner fuels among global container shipping companies. Companies are categorized as first movers, second movers, and last movers based on their environmental efficiency. This categorization provides a new perspective on strategic differentiation and improvement tactics for each group. It allows for the development of strategic frameworks tailored to the unique positions of different shipping companies, aiding them achieve the International Maritime Organization’s net-zero target by 2050. The study’s originality lies in its use of DEA to evaluate efficiency and backcasting for strategic planning. This combination provides policymakers and industry leaders with actionable insights and a robust methodological framework for promoting sustainable maritime management. The dual approach not only contributes to academic literature, but also aids in navigating the complexities of green transitions in the shipping industry.